2021
DOI: 10.3390/nu13020459
|View full text |Cite
|
Sign up to set email alerts
|

Application of Molecular Hydrogen as an Antioxidant in Responses to Ventilatory and Ergogenic Adjustments during Incremental Exercise in Humans

Abstract: We investigated effects of molecular hydrogen (H2) supplementation on acid-base status, pulmonary gas exchange responses, and local muscle oxygenation during incremental exercise. Eighteen healthy, trained subjects in a randomized, double-blind, crossover design received H2-rich calcium powder (HCP) (1500 mg/day, containing 2.544 µg/day of H2) or H2-depleted placebo (1500 mg/day) for three consecutive days. They performed cycling incremental exercise starting at 20-watt work rate, increasing by 20 watts/2 min … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…The results of analyses showed that this dose of HCP significantly increased PCO 2 and HCO 3 − and showed a slight tendency toward acidosis at rest (i.e., a slightly but not significantly lowered pH). In the HCP group, the increased HCO 3 − was also reflected in the significantly increased BE, and the tendency toward acidosis in pH as a result of the increased PCO 2 could be additionally augmented as an effect of HCP’s antioxidant properties and the suppression of reactive oxygen species (ROS), as a reduced ventilatory sensitivity to hypercapnia following antioxidant administration has been observed in several studies [ 7 , 24 , 25 ]. However, further examination of the direct effect of HCP on ROS is needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of analyses showed that this dose of HCP significantly increased PCO 2 and HCO 3 − and showed a slight tendency toward acidosis at rest (i.e., a slightly but not significantly lowered pH). In the HCP group, the increased HCO 3 − was also reflected in the significantly increased BE, and the tendency toward acidosis in pH as a result of the increased PCO 2 could be additionally augmented as an effect of HCP’s antioxidant properties and the suppression of reactive oxygen species (ROS), as a reduced ventilatory sensitivity to hypercapnia following antioxidant administration has been observed in several studies [ 7 , 24 , 25 ]. However, further examination of the direct effect of HCP on ROS is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Following our previous study’s protocol [ 7 ], the subjects were familiarized with all measurement techniques, and a familiarization test was conducted a few weeks prior to the start of the experiments; the testing sessions were separated by a 1- to 2-week washout period. All sessions were completed in Doshisha University in a custom-made environmental chamber (model LP-2.5PH-SS, NK Systems, Osaka, Japan) maintained at a temperature of 25 °C and 50% relative humidity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An improvement in clinical symptoms was seen in a significantly higher percentage of patients in the treatment group, who inhaled a mixture of H 2 and O 2 , than in patients in the control group, who received classic oxygen therapy, although randomization was not applied because of the urgency to deal with the outbreak (Guan et al, 2020b ). Similarly, application of H 2 improves O 2 utilization rate, reduces O 2 consumption, and improves exercise endurance as in healthy humans (Alharbi et al, 2021 ). Inhalation of the mixed gas of O 2 and H 2 can expand the bronchioles and reduce the inspiratory effort, and thus promote the absorption of O 2 by the alveoli (Zhou et al, 2019 ).…”
Section: Biological Effects Of Hydrogenmentioning
confidence: 99%